-2y/2=8-3x/2

Simple and best practice solution for -2y/2=8-3x/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y/2=8-3x/2 equation:


x in (-oo:+oo)

(-2*y)/2 = 8-((3*x)/2) // - 8-((3*x)/2)

(3*x)/2+(-2*y)/2-8 = 0

3/2*x-y-8 = 0 // + -y-8

3/2*x = -(-y-8) // : 3/2

x = (-(-y-8))/3/2

x = 2/3*(y+8)

x = 2/3*(y+8)

See similar equations:

| 2/3(9x-12)=24 | | 2L+2(10)=60 | | f(x-1)=4x^2+5x+7 | | X+3x-1=33 | | 16+7c=51 | | x^2+.12x-.054=0 | | 2w=2.56 | | -28+p=(p-10) | | -26/50 | | 22x-3.5=18.5 | | y+6(y-9)= | | y=41x-(88000+33x) | | 7x+6x+3+8=10x+5+2x | | 13x+.64x=100 | | 6x-14-4x=6x-9 | | (4X+7)+(2X-16)= | | 7(4y-9)-(2y+6)= | | 3y-10=x | | u=5(8n+35)+6(n+1) | | 5n+9=3n-1 | | (4c^8d^-6)/8d^3)^-1 | | (4X+7)+(2-16)= | | 5m=18+2m | | log(9x)=1 | | (2+y)(2y+3)=0 | | x=-14+3(4) | | (-4.5)+4.9+3.4= | | 18+10=m | | 2.5x-3(x+1)=12 | | 4x^9n+4=256 | | -70+15y+2y=-2 | | 3/9y-5=-2 |

Equations solver categories